Clinical presentation of new onset refractory status epilepticus in children (the pSERG cohort). (6th June 2021) - Sculier, Claudine; Barcia Aguilar, Cristina; Gaspard, Nicolas; Gaínza‐Lein, Marina; Sánchez Fernández, Iván; Amengual‐Gual, Marta; Anderson, Anne; Arya, Ravindra; Burrows, Brian T.; Brenton, James N.; Carpenter, Jessica L.; Chapman, Kevin E.; et al.
Abstract: Objective: We aimed to characterize the clinical profile and outcomes of new onset refractory status epilepticus (NORSE) in children, and investigated the relationship between fever onset and status epilepticus (SE). Methods: Patients with refractory SE (RSE) between June 1, 2011 and October 1, 2016 were prospectively enrolled in the pSERG (Pediatric Status Epilepticus Research Group) cohort. Cases meeting the definition of NORSE were classified as "NORSE of known etiology" or "NORSE of unknown etiology." Subgroup analysis of NORSE of unknown etiology was completed based on the presence and time of fever occurrence relative to RSE onset: fever at onset (≤24 h), previous fever (2 weeks–24 h), and without fever. Results: Of 279 patients with RSE, 46 patients met the criteria for NORSE. The median age was 2.4 years, and 25 (54%) were female. Forty (87%) patients had NORSE of unknown etiology. Nineteen (48%) presented with fever at SE onset, 16 (40%) had a previous fever, and five (12%) had no fever. The patients with preceding fever had more prolonged SE and worse outcomes, and 25% recovered baseline neurological function. The patients with fever at onset were younger and had shorter SE episodes, and 89% recovered baseline function. Significance: Among pediatric patients with RSE, 16% met diagnostic criteria for NORSE,  including the subcategory of febrile infection‐related epilepsy syndrome (FIRES). Pediatric NORSE cases may also overlap with refractory febrile SE (FSE). FIRES occurs more frequently in older children, the course is usually prolonged, and outcomes are worse, as compared to refractory FSE. Fever occurring more than 24 h before the onset of seizures differentiates a subgroup of NORSE patients with distinctive clinical characteristics and worse outcomes.